Dataveillance, Design, and the Demise of Interpretive Flexibility - Aho, Brett (Surveillance & Society, 2025)
Over the past decade, new technologies have been increasingly deployed in a manner that allows designers to remotely collect usage data, facilitating the development and rollout of updates and adjustments after their release. By retaining control over product stabilization, designers can discourage technologies from being used in manners other than that which they prescribe, thereby reducing interpretive flexibility. As a result, end users are increasingly shepherded towards use-patterns that reflect the interests of designers. This paper explores this agential shift using three case studies. The first considers the evolution of a video game series, exploring how expanding data-collection practices in subsequent releases changed design processes and user experiences. The second case examines the evolution of social media design and the rise of algorithmic nudging. The third case broadly analyzes humanitarian design, demonstrating how dataveillance has expanded beyond consumer electronics. By maintaining control over use-patterns, designers can reduce uncertainty and increase profitability. However, these subtle power shifts also have consequences for user agency and interpretive flexibility, reanimating debates about technological determinism.